"Loser" or "Popular"?: Neural response to social status words in adolescents with major depressive disorder. (December 2017) - Silk, Jennifer S.; Lee, Kyung Hwa; Kerestes, Rebecca; Griffith, Julianne M.; Dahl, Ronald E.; Ladouceur, Cecile D.
Highlights: Depressed youth show reduced brain activation to social status words in areas involved in social cognitive processing (STC and MPFC). Healthy youth don't differ in social cognitive processing of social status (compared to neutral) words in these brain regions. Depressed youth also show reduced DLPFC and fusiform gyrus response to negative, compared to positive, social status words. Age, but not pubertal status, was positively correlated with activation in MPFC to social status words. Abstract: Concerns about social status are ubiquitous during adolescence, with information about social status often conveyed in text formats. Depressed adolescents may show alterations in the functioning of neural systems supporting processing of social status information. We examined whether depressed youth exhibited altered neural activation to social status words in temporal and prefrontal cortical regions thought to be involved in social cognitive processing, and whether this response was associated with development. Forty-nine adolescents (ages 10–18; 35 female), including 20 with major depressive disorder and 29 controls, were scanned while identifying the valence of words that connoted positive and negative social status. Results indicated that depressed youth showed reduced late activation to social status (vs neutral) words in the superior temporal cortex (STC) and medial prefrontal cortex (MPFC); whereas healthy youth did not show any significant differences between word types. Depressed youth also showed reduced late activation in the dorsolateral prefrontal cortex and fusiform gyrus to negative (vs positive) social status words; whereas healthy youth showed the opposite pattern. Finally, age was positively associated with MPFC activation to social status words. Findings suggest that hypoactivation in the "social cognitive brain network" might be implicated in altered interpersonal functioning in adolescent depression.